A combined experimental and numerical investigation on damage characteristics of ice sheet subjected to underwater explosion load. (October 2020) - Wang, Ying; Qin, Yezhi; Yao, Xiongliang
Highlights: This paper adopts the Arbitrary-Lagrangian–Eulerian (ALE) algorithm of LS-DYNA software to build a numerical simulation model solving FSI issue of underwater explosion for ice dynamic response researching. The efficiency and accuracy of the underwater explosion material and numerical model are validated by comparing with experimental results. The damage characteristics and dynamic response of the ice sheet subjected to underwater explosion load are analyzed, and the mechanism of the ice sheet and fluid interaction are revealed. The effects of the main factors affecting the efficiency ice-breaking for underwater explosion are investigated and discussed. And a predicted formula for the damaged area is put forward. Abstract: The objective of this study is to investigate the damage characteristics response of the ice sheet and reveal the mechanism of ice-breaking subjected to the underwater explosion. The Arbitrary-Lagrangian–Eulerian (ALE) algorithm for the fluid–structure-interaction issue of the LS-DYNA software was adopted. The efficiency and accuracy of the underwater explosion material and numerical model were studied. Besides, the reliability of the numerical model for ice-breaking subjected to the underwater explosion was validated further by comparing it with the experiment test. Then, the damage characteristics and dynamic response of the ice sheet suffering from underwater explosion load are investigated. Besides, the shock pressure propagating characteristics and bubble dynamics were analyzed. The results show that the shock wave can cause the ice sheet initial damage to the ice sheet, and the bubble movement and water jet have significance on ice fractured and crushed. Then the effects of the main factors affecting the efficiency ice-breaking subjected to the underwater explosion were investigated and discussed. A predicted formula for damage area is put forward, which can be available for guiding engineering ice-breaking underwater blast.